1994
DOI: 10.1017/s0022112094001837
|View full text |Cite
|
Sign up to set email alerts
|

Coherent structures in rotating three-dimensional turbulence

Abstract: Numerical simulations investigating the formation and stability of quasi-two-dimensional coherent vortices in rotating homogeneous three-dimensional flow are described. In a numerical study of shear flows Lesieur, Yanase & Métais (1991) found that cyclones (respectively anticyclones) with |ω2D| ∼ O(2Ω), where ω2D is the vorticity and Ω is the rotation rate, are stabilized (respectively destabilized) by the rotation. A study of triply periodic pseudo-spectral simulations (643) was undertaken in order to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
148
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 26 publications
14
148
0
1
Order By: Relevance
“…The rotating turbulence is still homogeneous ͑within the horizontal plane͒ but no longer 3C isotropic. Instead, based on the invariant maps one tends to classify the rotating turbulence as a 3D2C flow, consistent with other numerical simulations 22 Figure 12 shows the time-averaged temporal velocity correlation coefficients ͗ ii ͘ TA and ͗ ␣␣ ͘ TA ͑with ␣ = 1 and 3͒ for ͕H , ⍀ , I͖ = ͕50,1,4͖, ͕50,5,4͖, and ͕50,10,4͖. The correlation time is now scaled by the rotational time scale T ⍀ instead of the eddy turn-over time scale T e .…”
Section: A Characterization Of Parameter Tripletsˆ50 ω 4‰supporting
confidence: 84%
See 1 more Smart Citation
“…The rotating turbulence is still homogeneous ͑within the horizontal plane͒ but no longer 3C isotropic. Instead, based on the invariant maps one tends to classify the rotating turbulence as a 3D2C flow, consistent with other numerical simulations 22 Figure 12 shows the time-averaged temporal velocity correlation coefficients ͗ ii ͘ TA and ͗ ␣␣ ͘ TA ͑with ␣ = 1 and 3͒ for ͕H , ⍀ , I͖ = ͕50,1,4͖, ͕50,5,4͖, and ͕50,10,4͖. The correlation time is now scaled by the rotational time scale T ⍀ instead of the eddy turn-over time scale T e .…”
Section: A Characterization Of Parameter Tripletsˆ50 ω 4‰supporting
confidence: 84%
“…Numerical simulations have shown that the faster growth of certain integral length scales is also related to the inhibited energy cascade. [21][22][23] Among the most recent experimental studies are those by Baroud et al, 13,14 Morize and co-workers, 15,24 and by Davidson an co-workers. 16, 17 Baroud and co-workers studied the flow in a rotating annulus with forcing created by pumping water into ͑out of͒ the annulus through an inner ͑outer͒ ring of holes on the bottom of the annulus.…”
Section: Introductionmentioning
confidence: 99%
“…The breaking of asymmetry between cyclonic and anticyclonic vortices, which has been observed both in experiments [15,25,[28][29][30] and in numerical simulations [20,31,32], is a distinctive feature of rotating turbulent flows. Here we are interested to investigate how this asymmetry is influenced both by the rotation and the confinement of the flow.…”
Section: Cyclonic-anticyclonic Asymmetrymentioning
confidence: 82%
“…Several explanations have been proposed to explain this phenomenon. In particular, it has been shown that the cyclones and anticyclones have different stability properties [31] and different probabilities to be generated at finite Rossby number [33]. Moreover, the correlations between the strain tensor and the vorticity in isotropic turbulence can be responsible for the development of a positive skewness of vertical vorticity when the flow is suddenly subjected to rotation [34].…”
Section: Introductionmentioning
confidence: 99%
“…The Coriolis term breaks the parity invariance of the governing equation of the flow, and introduces a scale-independent time scale which induces two-dimensionalization at larger scales more effectively. Therefore, the Coriolis effect originates cyclone-anticyclone asymmetry with enhanced stretching of cyclonic vorticity and destabilization of anticyclonic one due to the centrifugal instability and the vortex tilting [4].To classify the flow properties in rotating systems, the Rossby number Ro, which is the ratio between the linear and nonlinear time scales, has been used [5]. Note that though various definitions of Ro are used in literature, the following facts are independent of its detailed definition.…”
mentioning
confidence: 99%